2015
DOI: 10.1007/s11104-015-2433-5
|View full text |Cite
|
Sign up to set email alerts
|

Intercropping affects the rate of decomposition of soil organic matter and root litter

Abstract: Aims Intercropping increases aboveground and belowground crop productivity, suggesting potential for carbon sequestration. Here we determined whether intercropping affects decomposition of soil organic matter (SOM) and root litter. Methods We measured in the laboratory and the field the breakdown of SOM, root litter of maize, wheat, or faba bean, litter mixtures, and a standard substrate (compost) in soils from a long term intercropping experiment. Results Soil organic matter from intercrop plots decomposed fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 46 publications
0
36
0
1
Order By: Relevance
“…Moreover, under NT systems, corn roots, which are more concentrated in surface soil layers (Silva et al, 2000), together with the deposition of plant residues, may have also contributed to increases in TOC and TN. It should be noted, that although the enhanced levels of TN may also be attributed to N fertilization in corn, the simultaneous increase in TOC suggests the possibility of synergy between C and N, whereby C sequestration enhances N sequestration, and vice versa (Cong et al, 2015). Diógenes et al (2013) found higher TOC values for corn intercropped with U. ruziziensis, when compared to this forage in monoculture.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, under NT systems, corn roots, which are more concentrated in surface soil layers (Silva et al, 2000), together with the deposition of plant residues, may have also contributed to increases in TOC and TN. It should be noted, that although the enhanced levels of TN may also be attributed to N fertilization in corn, the simultaneous increase in TOC suggests the possibility of synergy between C and N, whereby C sequestration enhances N sequestration, and vice versa (Cong et al, 2015). Diógenes et al (2013) found higher TOC values for corn intercropped with U. ruziziensis, when compared to this forage in monoculture.…”
Section: Resultsmentioning
confidence: 89%
“…However, differences in plant residue quality and chemical composition may affect SMB growth (Ferreira et al, 2011;Cong et al, 2015), which, in turn, may be positively related to N (NO 3 -and NH 4 + ) mineralization potential in the soil and, consequently, to its uptake by SMB (Burger & Jackson, 2003). Dourado-Neto et al (2010) highlighted that, in tropical agroecosystems, soil N pool can provide up to 79% of the total N uptake by plants, showing the importance of SOM preservation and of plant residue inputs for N availability to crops.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, our results question the extent of using C : N ratios alone to predict the soil response to residue input and consequences for greenhouse gas flux. While we cannot completely exclude a priming effect causing increased soil respiration following residue amendments (Fontaine et al ., ; Cong et al ., ), significant CO 2 release coupled to a relatively higher biomass loss of the same residues suggest that the newly added carbon source, rather than the existing carbon fraction in the soil was mineralized, in which case, priming effect would be minimal.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese researchers have actively engaged in quantitative studies on wheat-maize intercrop performance over the last two decades. Studies focused on quantification of yields (Li et al, 2001b), radiation use efficiency and water use efficiency (Fan et al, 2013), analyses of the soil carbon and nitrogen sequestration in the long term (Cong et al, 2015a;Cong et al, 2015b) and greenhouse gas emission Hu et al, 2016), and exploration of belowground root interactions in terms of nutrient mobilization and nutrient transfer between species (Zhang and Li, 2003). Often positive effects were found in those studies, such as higher land use efficiency, higher water use efficiency, greater carbon and nitrogen storage and less greenhouse gas emission per hectare in wheat-maize intercropping compared to sole wheat or sole maize.…”
Section: Wheat-maize Relay Strip Intercropping In Chinamentioning
confidence: 99%
“…Development of machinery for cultivating and harvesting intercrops is required to overcome this constraint. A market for such machinery may develop if the advantages of intercropping (high yield, better resource capture, building of soil organic matter, suppression of pests and diseases) are substantial and recognized (Brooker et al, 2015;Cong et al, 2015a).…”
Section: Scientific and Practical Implicationsmentioning
confidence: 99%